2002
DOI: 10.1161/01.cir.0000029804.61510.02
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Titin Isoform Expression in Pacing-Induced Cardiac Failure Give Rise to Increased Passive Muscle Stiffness

Abstract: Background-Titin contains a molecular spring segment that underlies passive myocardial stiffness. Myocardium coexpresses titin isoforms with molecular spring length variants and, consequently, distinct stiffness characteristics: the stiff N2B isoform (short spring) and more compliant N2BA isoform (long spring). We tested whether changes in titin isoform expression occur in the diastolic dysfunction that accompanies heart failure. Methods and Results-We used the tachycardia-induced dilated cardiomyopathy canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 41 publications
5
124
2
4
Order By: Relevance
“…Extracellular matrix function and myocyte adhesion capacity are decreased, and plasma catecholamines, endothelin, and renin activity are all increased. 16,17 Our paced NTG rabbits lacked any detectable ␣-MHC protein in the ventricles, a feature consistent with human DCM. 3,4 In the TG animals, the ␤-MHC promoter continued to express ␣-MHC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Extracellular matrix function and myocyte adhesion capacity are decreased, and plasma catecholamines, endothelin, and renin activity are all increased. 16,17 Our paced NTG rabbits lacked any detectable ␣-MHC protein in the ventricles, a feature consistent with human DCM. 3,4 In the TG animals, the ␤-MHC promoter continued to express ␣-MHC.…”
Section: Discussionsupporting
confidence: 60%
“…Rapid ventricular pacing results in depressed myocardial function in many species with clinical and laboratory findings very similar to that seen in human DCM. 16,17 We applied TIC to the ␣-MHC TG rabbits and developed a protocol similar to that of Jeron et al 18 (Figure 2). The initial cohort consisted of 6 TG and 7 NTG 15-month line 45 rabbits of mixed gender (2 females and 4 males in the TG group, 2 females and 5 males in the NTG group).…”
Section: Resultsmentioning
confidence: 99%
“…118 A reduced N2BA:N2B expression ratio was also seen in tachypaced dog hearts. 119,120 Taken together, eccentric remodeled hearts with systolic dysfunction (DCM/HFrEF/chronic ischemic cardiomyopathy) frequently seem to express higher N2BA proportions than healthy hearts ( Figure 5A), thereby reducing myofibrillar passive stiffness ( Figure 5B). An exception is the tachypaced dog HF model, which increases the proportion of stiff N2B titin.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 97%
“…The ratio of the N2BA to N2B isoforms affects passive tension in the heart with muscle containing higher N2BA proportions exhibiting lower tension at a given sarcomere length. The isoform ratio was shown to be altered by hypertension in the rat [16] and, artificially, by chronic pacing in the dog [17]. A genome-wide linkage scan found that exercise induced changes in cardiac stroke volume was linked to the titin gene chromosome region [18].…”
Section: Introductionmentioning
confidence: 99%